Feasibility study and business plan for manufacturing a 3 kW-electrical solar Stirling engine and dish for stand-alone power supply units - Kayofa, Lilongeni (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.